Coal Ash Disposal at Rotowaro Minesite: 1 Mt Non-Notified Consent - R J. Mills; B S. Sinclair; A G. Goldstone; D A. Fergusson (The Australasian Institute of Mining and Metallurgy, 2006)
In 2005, Solid Energy New Zealand Limited obtained non-notified consent for the disposal of 1Mt of coal ash at the Rotowaro minesite, forming part of a coal supply agreement with the Huntly Power Station. The consenting of major mine site activities has historically required wide consultation and involves notification of the application.   The risk and cost associated with consultation can be significantly reduced via a non-notified process. A non-notified consenting process necessitates environmental effects to be shown to be æless than minorÆ, which requires the combination of robust science and a pragmatic approach to design, assessment of environmental effects, and consenting issues.   Key issues examined included consideration of how to practically operate a significant disposal project within the confines of an operating mine, minimising the costs, civil and geotechnical design and practical issues associated with traditional disposal. Environmental issues specifically related to the coal ash, led to a site specific performance driven approach to management rather than relying on conventional prescriptive approaches. Environmental issues of concern include the leaching of boron and aluminium from ash into groundwater and mine water management systems where both boron and aluminium can occur at elevated levels.   Coal ash exhibits unusual geochemical characteristics reflecting the primary coal composition and the combustion process. The dominant coal type combusted at the Huntly Power Station is derived from Rotowaro and the resulting ash is cementitious and has a high alkalinity. As a result the disposal design is based on the characteristics of the ash itself rather than the material into, or onto which the ash is disposed. Non-notified status was able to be achieved through consideration of these key characteristics of the ash, ensuring that the dimensions of the disposal site and each location was designed to minimise the flow of groundwater through the ash and demonstrating that the physical ash disposal effects are less than minor compared to the consented mining operation.